The relationship between trust, belief and adherence among patients who complain of hypertension in Ghana - Kennedy Dodam Konlan; Kennedy Diema Konlan; Juliana Asibi Abdulai; Joel Afram Saah; Abdul Razak Doat; Roberta Mensima Amoah; Iddrisu Mohammed (Wiley, 2023)
Abstract Aim We determined the relationship between trust, belief and adherence among patients who complain of hypertension in Ghana. Design A cross‐sectional design was used. Method We sampled 447 Ghanaians with hypertension receiving care at the Korle Bu Teaching Hospital. Data were collected using a pre‐tested self‐administered questionnaire. Data analyses were conducted with the aid of Stata 15.0. Results There is low belief and trust in the biomedical treatment for hypertension. Only 36.9% of the respondents said they adhered to treatment with females expressing higher level of adherence. Trust and belief in allopathic care were associated with adherence to treatment. It is recommended that health workers identify effective ways of improving patients' trust in the allopathic care for hypertension through teaching and re‐enforcement models to enhance treatment adherence and reduce the complications of hypertension. Patient or Public Contribution.